Kombinasi Filter Pada Sistem Resirkulasi Terhadap Pertumbuhan Benih Ikan Nila (Oreochromis Niloticus) - Suparlan Suparlan; Azwar Thaib; Said Aprilizar; Nurhayati Nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Tilapia (Oreochromis niloticus) is one type of freshwater fish that is much in demand by the community because it has a high nutritional content so that many fish farmers cultivate these fish. Water quality is one of the factors that influence the enlargement of tilapia, therefore the use of combined filters (biological and chemical) in the recirculation system can be used as a solution. The purpose of this study was to determine the best growth of tilapia that was kept using a combined filter in the recirculation system. This study uses a comparison test as the treatment is treatment A; combined filter in the recirculation system, B; without recirculation. The parameters observed were survival rate, absolute weight growth, length growth and specific growth rate. The results showed that the use of combined filters in the recirculation system showed a significant effect on survival and not significantly different from absolute growth, length growth and specific growth rate. Treatment A is the best treatment with a survival rate of 100%, absolute weight growth of 3.44 grams, growth length of 5.73 cm and specific growth rate of 2.78%.